Incidence of pediatric long bone fractures at the university college hospital Ibadan - Ogunrewo, Tolulope O.; Oyewole, Olugboyega A.; Omoyeni, Richard A.; Balogun, Mosimabale J.; Okunola, Michael O. (International Journal of Research in Orthopaedics, 2020)
Background: Individuals within the paediatric age group sustain different types of fractures, as such the need to determine the incidence and pattern of long bone fractures among patients 16 years and below admitted through the different wards of admittance of the university college hospital Ibadan. Methods: This was a retrospective hospital-based study involving patients 16 years and below admitted through the accident and emergency department, the children emergency department, the neonatal ward and labour ward of the hospital between January 2013 and December 2018 at the university college hospital Ibadan. Using a proformal completed from the electronically stored data that captured the patient’s history, examination findings, X-ray film and treatment offered which was collected on a weekly basis. Results: 25.13% of the patients reviewed within the study period were paediatric patients. A total of 337 paediatric patients were reviewed. There were 124 female and 213 males with ratio (F:M-1:1.7). The fractures were mostly secondary to fall and road traffic crash accounting for 68.54% and 23.15% respectively. 65.12% of the fractures involve the bone of the upper limbs while 34.98% occur in the bones of the lower limbs. The radius and the ulnar bones are the most affected. Transverse fracture is the most common pattern observed. Conclusions: More than 20% of the reviewed population was in the paediatric age group and the radius and ulnar bones were the most commonly fractured bone in this age group. They usually follow trivial falls.